EVALUASI PROGRAM PRAKTEK BAHASA ARAB DI PONDOK PESANTREN ISLAM INTERNASION AL AL-ANDALUS - Dwi Wahyu Iskandar (Jurnal Kinerja, 2023)
This study aims to identify and analyze the evaluation of the Arabic language practice program at the Al-Andalus International Islamic Boarding School. This study uses a qualitative descriptive method with the CIPP evaluation approach. In this study the data collection techniques carried out by researchers were observation, interviews and documentation. After the data has been collected, an analysis is carried out with data reduction, data display and verification to obtain an overview of the implementation of the evaluation of the Arabic language practice program at the Al-Andalus International Islamic Boarding School. The results of the study show that: 1) the context evaluation component of the Arabic language training program is in accordance with the background of the program, the objectives of the program, the interests of the participants and the targets of the participants in participating in the program; 2) the input evaluation component in the Islamic boarding school environment is in accordance with the criteria, namely teachers who have and master 4 Arabic language competencies, namely; speaking, writing, reading and listening as well as having teaching experience. Meanwhile, in terms of facilities and infrastructure, more support is needed; 3) the process evaluation component is in accordance with the program design, namely it already has a foundation of objectives, timeframe, methods, strategies, in the implementation of the program students are actively involved in this practicum activity but not all strategies can be carried out, and 4) the product evaluation component of the practicum program implementation has went well and in line with expectations so as to be able to produce alumni who master Arabic both orally and in writing.